Epstein-Barr Virus (EBV) Genome and Expression in Breast Cancer Tissue: Effect of EBV Infection of Breast Cancer Cells on Resistance (Taxol) - Arbach, Hratch (2006)
Artículo científico -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 2006